THE CORRELATION BETWEEN STUDENT LISTENING ANXIETY AND LISTENING COMPREHENSION SKILL IN CRITICAL LISTENING CLASS - Huwaidah, Faiqohan Salsabila (ENGLISH JOURNAL, 2024)
ABSTRACT This study investigates the relationship between listening anxiety and listening comprehension in critical listening classes. The research is motivated by the crucial role of listening skills in learning English as a foreign language and the challenges posed by listening anxiety, which can affect comprehension. The objectives are to assess the impact of the Project-Based Learning (PjBL) method on reducing students' listening anxiety and to explore the correlation between listening anxiety and listening comprehension in these classes. The research employs a correlational study design to analyze the relationship between two variables: listening anxiety (independent variable) and listening comprehension (dependent variable). The study involved two critical listening classes with a total population of 41 students, from which a sample of 25% was selected. Data were collected using a questionnaire adapted from the Foreign Language Listening Anxiety Scale (FLLAS) and a multiple-choice listening comprehension test. Analysis was conducted using SPSS 20.0 to determine the relationship between listening anxiety and comprehension. The results indicate that the average listening anxiety score among students falls within the “very good” range (81–87), suggesting low anxiety levels. Conversely, the average listening comprehension score is classified as “low,” with scores ranging between 53 and 61. The study finds a significant inverse relationship between listening anxiety and comprehension, meaning that higher levels of listening anxiety are associated with poorer listening comprehension, while lower anxiety levels are linked to better comprehension. These findings suggest that reducing listening anxiety could enhance students' ability to understand spoken language in critical listening contexts.